TractCloud‐FOV: Deep Learning‐Based Robust Tractography Parcellation in Diffusion MRI With Incomplete Field of View - Yuqian Chen; Leo Zekelman; Yui Lo; Suheyla Cetin‐Karayumak; Tengfei Xue; Yogesh Rathi; Nikos Makris; Fan Zhang; Weidong Cai; Lauren J. O’Donnell (2025)
ABSTRACT Tractography parcellation classifies streamlines reconstructed from diffusion MRI into anatomically defined fiber tracts for clinical and research applications. However, clinical scans often have incomplete fields of view (FOV) where brain regions are partially imaged, leading to partial, or truncated fiber tracts. To address this challenge, we introduce TractCloud‐FOV, a deep learning framework that robustly parcellates tractography under conditions of incomplete FOV. We propose a novel training strategy, FOV‐Cut Augmentation (FOV‐CA), in which we synthetically cut tractograms to simulate a spectrum of real‐world inferior FOV cutoff scenarios. This data augmentation approach enriches the training set with realistic truncated streamlines, enabling the model to achieve superior generalization. We evaluate the proposed TractCloud‐FOV on both synthetically cut tractography and two real‐life datasets with incomplete FOV. TractCloud‐FOV significantly outperforms several state‐of‐the‐art methods on all testing datasets in terms of streamline classification accuracy, generalization ability, tract anatomical depiction, and computational efficiency. Overall, TractCloud‐FOV achieves efficient and consistent tractography parcellation in diffusion MRI with incomplete FOV.